Leadership Lessons for a New Battalion Surgeon. Issue 5 (3rd May 2021) - Maciuba, Joseph M; Griffith, Matthew E
ABSTRACT: Military medical corps officers often do not have experience with line units until after residency. This case demonstrates the importance of understanding the flow of information within an operational setting. The case also highlights the challenges of advocating for patients as a young officer and physician.